2021
DOI: 10.15420/ecr.2021.31
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Colchicine Treatment and Clinical Outcomes in Patients with Coronary Artery Disease: Systematic Review and Meta-analysis

Abstract: Background: The authors examined the association between colchicine treatment and clinical outcomes in patients with coronary artery disease. Methods: They performed a meta-analysis of randomised controlled trials (RCTs) involving patients with coronary artery disease receiving add-on colchicine to standard treatment compared with standard treatment. They used a mixed-effects Poisson regression model with random intervention effects to estimate the pooled incidence rate ratios (IRR) with 95% CI. Results: Ten R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…In the peri-procedural period of PCI, our study concluded that the statistics of all-cause mortality events, ISR, and MI were not meaningful, However, they were relevant in reducing the occurrence of post-procedural MACE and preventing in-stent thrombosis, which accords with the conclusions of several recent systematic reviews (33-35). In addition, in a previous meta-analysis of colchicine in CAD, colchicine was useful in avoiding stroke in CAD patients, as demonstrated by a systematic study (36); this study (37) supports the administration of low doses to decrease the occurrence of postoperative adverse events; colchicine decrease the risk of associated cardiovascular events by reducing levels of inflammatory factors, and both studies are consistent with our opinion (38,39); however, this study (40) found colchicine to be effective in preventing recurrent myocardial infarction, which may be related to the fact that t PCI was not used to treat the bulk of the study's experimental group. Nevertheless, none of the previous research assessed the effectiveness of colchicine at various intervals during the PCI perioperative period.…”
Section: Comparison With Previous Systematic Reviews and New Findingsmentioning
confidence: 74%
“…In the peri-procedural period of PCI, our study concluded that the statistics of all-cause mortality events, ISR, and MI were not meaningful, However, they were relevant in reducing the occurrence of post-procedural MACE and preventing in-stent thrombosis, which accords with the conclusions of several recent systematic reviews (33-35). In addition, in a previous meta-analysis of colchicine in CAD, colchicine was useful in avoiding stroke in CAD patients, as demonstrated by a systematic study (36); this study (37) supports the administration of low doses to decrease the occurrence of postoperative adverse events; colchicine decrease the risk of associated cardiovascular events by reducing levels of inflammatory factors, and both studies are consistent with our opinion (38,39); however, this study (40) found colchicine to be effective in preventing recurrent myocardial infarction, which may be related to the fact that t PCI was not used to treat the bulk of the study's experimental group. Nevertheless, none of the previous research assessed the effectiveness of colchicine at various intervals during the PCI perioperative period.…”
Section: Comparison With Previous Systematic Reviews and New Findingsmentioning
confidence: 74%
“… 62 A previous meta-analysis has also revealed a significant association between the administration of colchicine and AEs and suggested that higher dose was harder to be intolerable. 63 Undoubtedly, the adverse effects caused by higher dose will compromise its therapeutic benefits, therefore leading to the result that higher dose is inferior to lower dose in the therapeutic efficacy. Thus, based on the possible mechanisms of colchicine in exerting anti-inflammation, it is rational to extend the usage of colchicine from secondary prevention to primary prevention for cardiovascular diseases, especially low dose of colchicine 64 ; however, this hypothesis should be evaluated by future studies, such as an ongoing study registered on ClinicalTrials.gov.…”
Section: Discussionmentioning
confidence: 99%
“… 66 , 67 Nevertheless, such benefits were not attributed to a mortality benefit in this network meta-analysis, which was consistent with the findings of previous meta-analyses. 20 , 63 , 68 It should not be ignored that various disease types were evaluated in eligible studies, therefore inevitably introducing bias to compromise mortality benefit. Moreover, we cannot also eliminate the influence of variations in follow-up durations on mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, aging is exacerbating this trend [ 1 , 2 ]. Therefore, many clinical researchers are committed to exploring residual risk factors in CVD cases, discovering novel targets for intervention and formulating individualized and precise treatment plans [ 3 , 4 , 5 ]. Considered a critical risk factor for CAD, type 2 diabetes mellitus (T2DM) is also rising in terms of prevalence [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%